2015
DOI: 10.5539/jas.v7n3p148
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Associations Analysis for Fruit Yield and Its Contributing Traits of Indeterminate Tomato (Solanum lycopersicum L.) Germplasm under Open Field Condition

Abstract: The study was initiated to generate genetic information on characters associations for tomato germplasm under open field condition. Nineteen indeterminate tomato germplasm were evaluated to estimate the nature and magnitude of associations of different characters with fruit yield and among themselves at Vegetable Research Farm, Department of Horticulture, SHIATS, Allahabad (India) during 2012-2013. The experiment was conducted using a Randomized Complete Block Design (RCBD) with three replications. Estimates o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 31 publications
8
16
0
Order By: Relevance
“…Ascorbic acid (mg/100 g) showed significant and positive association with number of fruits plant -1 , fruit set percentage and TSS at genotypic and phenotypic level. The result was in full agreement with earlier studies by Meena and Bahadur (2015b) for TSS. Path coefficient analysis: Yield is the sum total of the several component characters which directly or indirectly contributed to it.…”
Section: Analysis Of Variancesupporting
confidence: 83%
See 2 more Smart Citations
“…Ascorbic acid (mg/100 g) showed significant and positive association with number of fruits plant -1 , fruit set percentage and TSS at genotypic and phenotypic level. The result was in full agreement with earlier studies by Meena and Bahadur (2015b) for TSS. Path coefficient analysis: Yield is the sum total of the several component characters which directly or indirectly contributed to it.…”
Section: Analysis Of Variancesupporting
confidence: 83%
“…This is in agree-ment with the results found by Ogwulumba and Ugwuoke (2013) genotypic and phenotypic level, indicating that fruit yield may be obtained in an indirect manner with selection for increase in the number of fruits per plant. Similar types of findings were also reported by Das et al (1998), Haydar et al (2007), Hidayatullah et al (2008), Islam et al (2010), for fruit yield plant -1 , Meena and Bahadur (2015b) for fruit set percentage and fruit yield plant -1 . Its association with the character like fruit weight, radial diameter of fruit and leaf curl incidence was negative and significant which indicated that as the number of fruits increases, the individual fruit weight and radial diameter would decreases.…”
Section: Analysis Of Variancesupporting
confidence: 78%
See 1 more Smart Citation
“…Previous studies have reported that positive association between yield and total number of fruits per plant is frequently detected on populations derived from different parental germplasm. Meena and Bahadur (2015) observed on indeterminate tomato that yield had a low correlation with total number of fruits per plant (0.19). However, McGiffen et al (1994), in processing tomato, reported a higher positive correlation value between yield and total number of fruits per plant (r = 0.76).…”
Section: Correlation Analysis Among the Traits Studiedmentioning
confidence: 82%
“…Sewall Wright (1921) is considered the first one that applied path analysis technique in genetics to quantify interrelationships, while the first application of this technique in breeding reported by Dewey and Lu (1959). In spite of much previous studies on path analysis in plant breeding and the appraisal of the available literature on tomato (Maurya et al 2011;Manoj 2011;Roa et al 2013;Pemba et al 2014;Meena and Bahadur 2015), this investigation is the first report applying path analysis to describe the cause and effect of electrolytes leakage on yield as a form of indirect selection for heat tolerance in tomato. According to our results, it could be recommended that the utilization of electrolytes leakage in tomato as indirect selection in early stage of plant development for discover the promising genotypes and discard the susceptible ones.…”
Section: Path Coefficient Analysismentioning
confidence: 99%